2022
DOI: 10.1093/pcp/pcac031
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of Lignin Monomer Composition Combined with the Introduction of Monolignol Conjugate Biosynthesis Leads to Synergistic Changes in Lignin Structure

Abstract: The complexity of lignin structure impedes efficient cell wall digestibility. Native lignin is composed of a mixture of three dominant monomers, coupled together through a variety of linkages. Work over the past few decades has demonstrated that lignin composition can be altered through a variety of mutational and transgenic approaches such that the polymer is derived almost entirely from a single monomer. In this study, we investigated changes to lignin structure and digestibility in Arabidopsis thaliana in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…This is consistent with most other work in the literature that either shows no change, or a reduction in saccharification, in F5H -suppressed plants, and an increase in saccharification when F5H is overexpressed and S lignin proportion increased. Several papers demonstrate that the predominantly G-lignin in the Arabidopsis fah1 F5H mutant impedes saccharification compared to wild-type lignin after liquid hot water pretreatment ( Li et al., 2010 ) or maleic acid treatment ( Ciesielski et al., 2014 ), although weak alkaline pretreatment reveals no change to saccharification ( Smith et al., 2022 ). On the other hand, Atf5h1 T-DNA insertion mutants allelic to fah1 did show an improved saccharification when no pretreatment was used ( van Acker et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with most other work in the literature that either shows no change, or a reduction in saccharification, in F5H -suppressed plants, and an increase in saccharification when F5H is overexpressed and S lignin proportion increased. Several papers demonstrate that the predominantly G-lignin in the Arabidopsis fah1 F5H mutant impedes saccharification compared to wild-type lignin after liquid hot water pretreatment ( Li et al., 2010 ) or maleic acid treatment ( Ciesielski et al., 2014 ), although weak alkaline pretreatment reveals no change to saccharification ( Smith et al., 2022 ). On the other hand, Atf5h1 T-DNA insertion mutants allelic to fah1 did show an improved saccharification when no pretreatment was used ( van Acker et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Populus tomentosa , downregulating F5H expression by manipulating miR6443, a microRNA that regulates S lignin biosynthesis, increases G units and reduces S units in lignin and lowers sugar yield after saccharification with both alkaline or acidic pretreatments ( Fan et al., 2020 ). Conversely, increasing F5H expression increases S lignin and saccharification in Arabidopsis after alkaline pretreatment ( Ciesielski et al., 2014 ; Smith et al., 2022 ), or maleic acid ( Sakamoto et al., 2020 ), or liquid hot water pretreatment ( Li et al., 2010 ) and in poplar after pretreatments with alkali ( Lapierre et al., 2021 ) or acid/alkali ( Fan et al., 2020 ). In the rice F5H1 CRISPR knock-out lines, saccharification efficiency was lowered compared to wild type only when using hot water pretreatment and unchanged with dilute acidic or alkaline pretreatments ( Takeda et al., 2019b ), whereas in switchgrass up- or down-regulation of F5H did not affect saccharification ( Wu et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important here to clearly delineate those phenolic monomers deriving from the core lignin (and therefore involving real depolymerization reactions) from those deriving from such pendent groups. This distinction is particularly noteworthy because these components simply acylate the biomass and can therefore be readily “clipped off” by hydrolysis reactions that are much milder than those required to cleave ethers. ,,, Because of the ability to derive valuable commodity chemicals from these esters (or the acids released from them), research into elevating their levels on the plant cell wall is ongoing. ,, These phenolates arise from biomass sources that derive their lignins, in part, from monolignol conjugates, such as the monolignol p -coumarates (ML- p CA) in grasses and monolignol p -hydroxybenzoates (ML- p HB) in the separately delineated hardwoods in Table from willow ( Salix ), poplar and aspen ( Populus ), and palm (Arecaceae) . In a more basic sense, it allows us to more clearly define how the core lignins behave in these classes of biomass, how important the phenolic monomers from these pendent groups may be, and how they might affect the distribution of phenolic monomers in the product mix (because of the competing hydrolysis and hydrogenolytic pathways, as illustrated in Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…We chose only a single softwood for the simple reason that studies over many decades have shown the lignins to be incredibly structurally similar, even back to the ancient gymnosperm Ginkgo . In fact, guaiacyl lignins produced in angiosperms by knocking out the hydroxylase [ferulate 5-hydroxylase (F5H)] crucial for syringyl lignin production are also similar . However, lignins derived from a single monolignol remain complex, with no defined sequences of units because of the combinatorial radical coupling nature of lignification, and the number of isomers possible for any oligolignol is astronomical because the coupling reactions are completely racemic. , The distribution of interunit linkage types is near-invariant, however, attesting to the similar endwise-coupling process of in planta lignification that is almost certainly radical-limited and controlled by diffusion and slow monomer supply …”
Section: Resultsmentioning
confidence: 99%
“…Studies of different naturally occurring or transgenic and mutant plants have led to the discovery that plants can tolerate large shifts in lignin composition, often without visible effects on plant development and morphology ( Meyer et al, 1998 ; Marita et al, 1999 ; Franke et al, 2000 ; Stewart et al, 2009 ; Eudes et al, 2017 ; de Vries et al, 2018 ). This notion has steered research toward the biosynthesis and incorporation of alternative monomers into the lignin ( Grabber et al, 2008 , 2010 , 2019 ; Vanholme et al, 2012 ; Smith et al, 2015 , 2022 ; Mottiar et al, 2016 ; del Río et al, 2022 ). Enhancing the incorporation of atypical monomers that are rare, or even absent, in the lignin of wild-type (WT) plants could permit a more efficient conversion of lignocellulosic biomass for the industry while maintaining the biological role of lignin.…”
Section: Introductionmentioning
confidence: 99%